1997
DOI: 10.1038/sj.hdy.6881970
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation in the scallop Pecten maximus (L.) assessed by a PCR-RFLP method

Abstract: Two PCR-RFLP mitochondrial DNA (nitDNA) markers were developed through the cloning and sequencing of mtDNA from the scallop Pecten maximus, and were used to study genetic differentiation of UK and Atlantic coast populations of this species. Although no distinct pattern of mtDNA haplotype frequencies was apparent and no diagnostic haplotypes were identified for any population, sequence divergence data provided convincing evidence that a P maximus sample taken from Muiroy Bay, Eire, a semi-enclosed sea lough, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…However, great scallops are also commercially bottom cultured at Mulroy Bay, which could potentially lead to changes in allele frequencies [69] even if scallop production is mainly based on wild-caught spat. Regardless of the exact explanation, our results are consistent with previous studies based on mitochondrial DNA and random amplified fragment polymorphisms that also found genetic differences between Mulroy Bay and other sites [26][27][28]. Interestingly, Mulroy Bay is an important population in the sense that it has been repeatedly used as a source of spat for scallop aquaculture both in Ireland and more widely across Europe [70].…”
Section: Comparison Of Microsatellite and Rad Sequencing Datasupporting
confidence: 92%
See 1 more Smart Citation
“…However, great scallops are also commercially bottom cultured at Mulroy Bay, which could potentially lead to changes in allele frequencies [69] even if scallop production is mainly based on wild-caught spat. Regardless of the exact explanation, our results are consistent with previous studies based on mitochondrial DNA and random amplified fragment polymorphisms that also found genetic differences between Mulroy Bay and other sites [26][27][28]. Interestingly, Mulroy Bay is an important population in the sense that it has been repeatedly used as a source of spat for scallop aquaculture both in Ireland and more widely across Europe [70].…”
Section: Comparison Of Microsatellite and Rad Sequencing Datasupporting
confidence: 92%
“…Consistent with knowledge of the life history of this species, previous genetic studies variously using allozymes, mitochondrial DNA and random amplified fragment polymorphisms have revealed very little in the way of population structure within the British Isles or France, with the exception of a single commercially cultured population at Mulroy Bay in Northern Ireland [26][27][28]. More recently, a larger pan-European study found evidence for two genetically distinct populations, one in Norway and the other comprising a number of Atlantic coastal populations sampled along a latitudinal gradient from Ireland to Spain [29].…”
Section: Introductionmentioning
confidence: 55%
“…All oysters were sent live to the laboratory, where they were opened and DNA was extracted from the gill tissue using a CTAB (hexadecyltrimethyl ammonium bromide) and phenol chloroform extraction method (Sambrook et al, 1989;Wilding et al, 1997). The four microsatellite loci used in the study were: Oedu.HA1, Oedu.HA7, Oedu.HA21, and Oedu.HA11a, with primer sequences and polymerase chain reaction (PCR) conditions as described in Sobolewska etal.…”
Section: Methodsmentioning
confidence: 99%
“…Mulroy Bay, an enclosed sea loch in Ireland, has been shown to differ from the rest of the UK using both mitochondrial DNA and Randomly Amplified Polymorphic DNA markers (RAPD) (Heipel et al,. ,,1998, 1999; Wilding et al, 1997), and that a site to the east of the Isle of Man was distinct from the western sites (Heipel et al, 1998, 1999). The same mitochondrial study also suggested that Plymouth was distinct from the Irish Sea samples but there was a strange result in that the RAPD markers showed high similarity between Plymouth and the northern most Isle of Man sites but not with the southernmost ones.…”
Section: Introductionmentioning
confidence: 98%